2003
DOI: 10.1002/adma.200305065
|View full text |Cite
|
Sign up to set email alerts
|

Polymer–Clay Nanocomposite Foams Prepared Using Carbon Dioxide

Abstract: drop of the suspension on a TEM grid, and letting the solvent evaporate slowly in a fume hood. XRD patterns were recorded on powder samples using a Philips PW1710 diffractometer (Cu Ka radiation, k = 1.54056 ) at a scanning rate of 0.02 s ±1 for 2h in the range of 10 to 70. UV-vis spectra were measured using a diode array spectrophotometer (Hewlett Packard 8452 A, Palo Alto, CA) with a resolution of 2 nm. Photoluminescence spectra were recorded using a luminescence spectrophotometer (Perkin Elmer LS-50B, Norwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
231
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(242 citation statements)
references
References 20 publications
6
231
0
5
Order By: Relevance
“…The foam morphology and properties greatly depend on the inclusion of nanoparticles. It has been reported that nanoparticles exhibit improved nucleation efficiency in the polymeric foaming processes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. With a low particle loading, microcellular foams with improved uniformity in foam morphology can be produced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The foam morphology and properties greatly depend on the inclusion of nanoparticles. It has been reported that nanoparticles exhibit improved nucleation efficiency in the polymeric foaming processes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. With a low particle loading, microcellular foams with improved uniformity in foam morphology can be produced.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, traditional thermoplastic foams, especially those generally considered as the insulation materials, are less attractive for these applications due to their inferior mechanical strength, poor surface quality, and low thermal and dimensional stability. In light of this, using nanoparticles to reinforce polymer foams has gained particular attention lately [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The foam morphology and properties greatly depend on the inclusion of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have concluded that when nanofillers are dispersed properly an effective nucleating effect, accompanied by an improvement in physical properties, is obtained. For instance, Zhen et al [13] demonstrated the high impact of the filler delamination level on the polymer foamability. They observed a higher cell nucleation efficiency with the exfoliated nanoclays than with the intercalated ones in both polystyrene (PS) and poly (methyl-methacrylate) (PMMA).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The morphologies generated via CO 2 processing are dependent on treatment pressures and temperatures, the physical properties of the polymer and the modifications thus induced as a result of contact with CO 2 . The solubility of CO 2 in a polymer leads to relaxation, chain mobility and hence reduction in the polymer's glass transition temperature (T g ).…”
Section: Introductionmentioning
confidence: 99%